1987
DOI: 10.1128/mcb.7.3.1129
|View full text |Cite
|
Sign up to set email alerts
|

Two transcriptional activators, CCAAT-box-binding transcription factor and heat shock transcription factor, interact with a human hsp70 gene promoter.

Abstract: We characterized the activity of a human hsp7O gene promoter by in vitro transcription. Analysis of 5' deletion and substitution mutants in HeLa nuclear extracts showed that the basal activity of the promoter depends primarily on a CCAAT-box sequence located at -65. A protein factor, CCAAT-box-binding transcription factor (CTF), was isolated from HeLa nuclear extracts and shown to be responsible for stimulation of transcription in a reconstituted in vitro system. DNase I footprinting revealed that CTF interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(122 citation statements)
references
References 40 publications
6
116
0
Order By: Relevance
“…Hsp70 induction is largely regulated at the transcriptional level in response to heat shock and mitogenic agents (41,42). The major identified regulatory site controlling Hsp70 expression is the HSE, a series of inverted repeats of the sequence 5Ј-NGAAN-3Ј that bind to oligomeric HSF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hsp70 induction is largely regulated at the transcriptional level in response to heat shock and mitogenic agents (41,42). The major identified regulatory site controlling Hsp70 expression is the HSE, a series of inverted repeats of the sequence 5Ј-NGAAN-3Ј that bind to oligomeric HSF.…”
Section: Discussionmentioning
confidence: 99%
“…6D, the Hsp70 promoter containing the GATA site mutation was not induced by p210 BCR-ABL , indicating that this sequence was essential for BCR-ABL-mediated transactivation. Previous work has shown that the major inducible regulator of Hsp70 expression is the HSE, an upstream cis sequence that binds to oligomeric heat shock factor formed in response to elevated temperature (41). To determine whether the BCR-ABL-GATA pathway interacted with the heat shock response-HSE path- way, cells transfected with Ϫ123 Hsp70/LUC in the presence or absence of p210 BCR-ABL were subjected to heat shock.…”
Section: Identification Of Bcr-abl Response Elements In the Hsp70mentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter of the hsp70 gene of humans, for example, contains binding sites for multiple transcriptional regulators (Morgan et al, 1987;Morgan, 1989). This gene can thus be expressed in response to stress as well as in response to various developmental or other cues.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail address: jbonner@bio.indiana.edu. † Present address: Parke Davis, Inc., Ann Arbor, MI.© 2000 by The American Society for Cell Biology 1739 (Morgan et al, 1987;Morgan, 1989). This gene can thus be expressed in response to stress as well as in response to various developmental or other cues.…”
mentioning
confidence: 99%